2011
DOI: 10.1021/jp203896w
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Li–Ca–B–H Complex Borohydride: Its Synthesis and Hydrogen Storage Properties

Abstract: The synthesis and hydrogen-storage properties of the mixed alkali metal and alkaline-earth metal borohydride are systematically investigated. It is found that mechanical milling a mixture of LiBH4 and CaCl2 with molar ratio of 3:1 in tetrahydrofuran (THF) forms a new LiBH4·Ca(BH4)2·2THF compound. Thermal analysis indicates that the decomposition process of the new compound involves four steps: (1) LiBH4·Ca(BH4)2·2THF decomposes first into high temperature phase of LiBH4, CaB6, and an intermediate phase Ca–B–H–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The permutation invariant polynomial neural network (PIP-NN) method [24] is used to fit the PES; PIP-NN is widely used in PES construction, and has been used for reactions such as H + LiH, [25] and O + + H 2 . [26] First, we transform the bond length to Q 1 = 1/r 1 , Q 2 = 1/r 2 + 1/r 3 , and Q 3 = 1/(r 1 *r 3 ), where r 1 is the bond length of the H 2 molecule, and r 2 and r 3 are correspond to the two MgH bond lengths.…”
Section: Potential Energy Surfacementioning
confidence: 99%
“…The permutation invariant polynomial neural network (PIP-NN) method [24] is used to fit the PES; PIP-NN is widely used in PES construction, and has been used for reactions such as H + LiH, [25] and O + + H 2 . [26] First, we transform the bond length to Q 1 = 1/r 1 , Q 2 = 1/r 2 + 1/r 3 , and Q 3 = 1/(r 1 *r 3 ), where r 1 is the bond length of the H 2 molecule, and r 2 and r 3 are correspond to the two MgH bond lengths.…”
Section: Potential Energy Surfacementioning
confidence: 99%
“…It was found that LiCa(BH4)3 exhibits improved (de)hydrogenation properties relative to the component phases. In 2011, Jiang et al studied synthesis and hydrogen storage properties of Li-Ca-B-H hydride [123]. They found that the first dehydrogenation temperature is about 70 o C, much lower than the pristine LiBH4 and Ca(BH4)2.…”
Section: Cation Substitutionmentioning
confidence: 99%
“…In the first report of NaÀMnÀW/SiO 2 , Li et al assumed that a surface cluster of tetrahedral WO 4 species (one W=O bond and three WÀOÀSi bonds) formed by surface reconstruction was the active site. [9] Further study by DFT calculations suggested that tetrahedral WO 4 species with a single bridging oxygen was the active site. [10] Later, they refined this proposal to a two metal oxide model, where gas phase O 2 and CH 4 were activated on Mn 3 + sites and W 6 + sites, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[13] In addition, a few research groups reported that the formation of MnWO 4 was reasonable for high performance of this catalyst. [14] It is important to note that traditional mechanism studies are generally based on the limited regulation of composition (approximate 5 wt%Na 2 WO 4 -2 wt%Mn-SiO 2 or 2 wt%Na 2 WO 4 -2 wt%Mn-SiO 2 , [15] ) and structure of NaÀMnÀW/ SiO 2 , [9,16] which might occasionally lead to biased conclusion. In addition, most researchers felt satisfied to find one of the optimized compositions with variable-controlling approach and easily overlooked other optimized compositions.…”
Section: Introductionmentioning
confidence: 99%